Materials for design. - Ballard Bell, Victoria, ....-; Rand, Patrick, 1950- (New York : Princeton Architectural Press, 2006)
As architecture programs throughout the country break out of the classroom and adopt the holistic methods of design/build programs, the need for a textbook that bridges the gap between construction materials and design sensibility is sorely needed. "Materials for Design" is that book. Students must be taught how a choice of material affects the form and look of a structure; they must also learn how inspired design can inject any material with true personality and zeal. Broken into five sections glass, wood, metals, plastics, and concrete "Materials for Design" makes a thorough study of each material's properties, followed by a series of 10 12 case studies of that material put to imaginative use by today's brightest architects from around the world. There is no other textbook on the market that tackles material details so thoroughly while presenting lush, inspired color photographs, plan drawings, and detailed architectural diagrams.
Keywords: Materialen; Ontwerpen